Fluidisation of lentil seeds during microwave drying and disinfection could prevent detrimental impacts on their chemical and biochemical characteristics. (July 2020) - Taheri, Saeedeh; Brodie, Graham; Gupta, Dorin
Abstract: A microwave fluidized bed has proven to be substantially more efficient than a conventional fluidized bed dryer in food and agriculture. However, its effect on the quality attributes of the grains, have not yet been fully discovered. In the present study, the effect of microwave fluidized bed drying with the aim of pest and pathogen control, utilising microwave powers of 0, 300, 400, 500 W (0, 3.6, 4.8 and 6 W g −1 dry seeds, respectively) and fluidizing air temperature of 50 and 60 °C, on the quality traits of lentil seeds were examined by measuring antioxidant enzyme activities, cooking quality and macronutrients analysis using Fourier transform infrared micro spectroscopy. A reduction in Peroxidase activity was observed at powers of 3.6 and 4.8 W g −1 and fluidizing air at 60 °C. The hardness of soaked and cooked seeds increased after drying at 6 W g −1 with both air temperatures and at 4.8 W g −1 with an air temperature of 60 °C. Based on the results of FTIR, no conformational changes in the protein secondary structure were observed at microwave powers of 0, 3.6, and 4.8 W g −1 . Therefore, controlling microwave radiation utilising hot air for agitation could prevent any negative effect on the grain quality attributes. Graphical abstract: Image 1 Highlights: Combination of fluidizing air and microwave radiation for lentil seeds treatment. No enzymatic change at low air temperature (50 °C) and powers of 3.6 and 4.8 W g −1 . Conformational changes in the protein secondary structure at high microwave power. Reduction in phosphate/protein ratio at high microwave power (6 W/g).